Music and Architecture - Garfias Santiago, Carmen (2019)
The interaction between different disciplines of the author of this article is always of interest, either by the musical studies as by the formation of architecture, it is for the strong curiosity in search for connections between these two disciplines.In this article, it comes to explaining the analogies, the relationships, the complementarity, the stimuli that have given one to other one and also the compositive complicity, across a trip that observes significant moments of the history where these two arts approach.